2001
DOI: 10.1159/000064338
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the Retinoblastoma Gene Expression in the Progression of Malignant Melanoma

Abstract: The retinoblastoma gene is a cell cycle regulator preventing cells from entering into S-phase. An altered expression of the retinoblastoma gene has been reported in the majority of human malignancies. The main aim of this study was to investigate retinoblastoma gene expression in the full spectrum of melanoma progression from naevus to melanoma metastases by applying immunohistochemistry and RT-PCR. All naevi with and without dysplasia showed high expression of the retinoblastoma gene. In primary melanomas, Rb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Results show a greater impact on p16 than on ARF, thus obtaining by predictive modelling an interpretation supporting coincident alterations in p53, or deletions in exon 1b, to achieve dual inactivation of RB and p53 pathways. These data add to the recurrent inactivation patterns reported above.Further support of the Yang et al viewpoint comes from the functional disruption of the RB locus, reported to occur in melanoma cell lines (Bartkova et al, 1996), a finding in keeping with the lack of RB expression shown in melanoma specimens (Korabiowska et al, 2001).Our own analysis of RB protein expression in cell lines harboring wild-type p16 and CDK4 genes showed that in three of eight cases studied RB was not detectable by immunoblotting. Notably, of the four of 41 tested cell lines expressing the p16 protein, three lines obtained from different lesions of a single patient, all harboring a mutated p53 and wild-type CDKN2A genes and detectable p16 and ARF proteins, lack RB protein expression (M. Rodolfo, unpublished results).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Results show a greater impact on p16 than on ARF, thus obtaining by predictive modelling an interpretation supporting coincident alterations in p53, or deletions in exon 1b, to achieve dual inactivation of RB and p53 pathways. These data add to the recurrent inactivation patterns reported above.Further support of the Yang et al viewpoint comes from the functional disruption of the RB locus, reported to occur in melanoma cell lines (Bartkova et al, 1996), a finding in keeping with the lack of RB expression shown in melanoma specimens (Korabiowska et al, 2001).Our own analysis of RB protein expression in cell lines harboring wild-type p16 and CDK4 genes showed that in three of eight cases studied RB was not detectable by immunoblotting. Notably, of the four of 41 tested cell lines expressing the p16 protein, three lines obtained from different lesions of a single patient, all harboring a mutated p53 and wild-type CDKN2A genes and detectable p16 and ARF proteins, lack RB protein expression (M. Rodolfo, unpublished results).…”
supporting
confidence: 76%
“…Further support of the Yang et al viewpoint comes from the functional disruption of the RB locus, reported to occur in melanoma cell lines (Bartkova et al, 1996), a finding in keeping with the lack of RB expression shown in melanoma specimens (Korabiowska et al, 2001).…”
mentioning
confidence: 64%
“…Participants provided background [17], mouse anti-pRb mAb NCL-Rb1 (Novocastra Laboratories, Newcastle-upon-Tyne, UK), mouse anti-p53 protein mAb NCL-p53-DO7 (Novocastra Laboratories), and mouse anti-p16 protein mAb (clone G175-405; BD PharMingen, San Diego, California, USA), respectively. Immunohistochemical analysis of melanomas using phospho-p44/42 MAPK, NCL-Rb1, NCL-p53-DO7, and G175-405 have previously been reported [6,7,[18][19][20]; however, immunohistochemical techniques were modified for optimal staining of our archival tissue. Staining with each antibody was performed separately, each in a single batch.…”
Section: Data Collectionmentioning
confidence: 99%
“…In small cell lung cancer (SCLC), for example, the prevalence of RB1 loss is more than 90% [12,13], while RB1 function in cervical cancer is suppressed by directly associating with HPV-E7 oncoprotein at a frequency of at least 90% [14,15]. A moderate frequency of RB1 dysfunction has been reported in several other types of cancers such as bladder, prostate cancers, and melanoma [16-18]. The RB1 loss is caused by several molecular events such as point mutations, deletion, or inactivation through associating viral proteins [19].…”
Section: Introductionmentioning
confidence: 99%